2010
DOI: 10.1002/meet.14504701202
|View full text |Cite
|
Sign up to set email alerts
|

Journal clustering through interlocking editorship information

Abstract: This paper is an exploration of mapping journals in library and information science (LIS) through interlocking editorship information. Forty-eight LIS journals are clustered into four clusters. Possible reasons for some boundary-spanning journals and ten journals uninvolved in interlocking editorship are given. Results suggest that interlocking editorship information is useful for clustering journals in LIS, and additional suggestions regarding LIS journal re-categorization are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…The MIS cluster is not very close (by author profile) to other clusters, as demonstrated by its isolated status in the figure. Similar status was founded for MIS journals by Ni and Ding () in their analysis of the editorial board members and Sugimoto et al. () in their analysis of MIS and IS&LS journals.…”
Section: Resultssupporting
confidence: 57%
“…The MIS cluster is not very close (by author profile) to other clusters, as demonstrated by its isolated status in the figure. Similar status was founded for MIS journals by Ni and Ding () in their analysis of the editorial board members and Sugimoto et al. () in their analysis of MIS and IS&LS journals.…”
Section: Resultssupporting
confidence: 57%
“…Journals listed in the Journal Citation Report (JCR) under the subject category IS-LS tend to cluster into three or four major sub-fields, including: management information systems (MIS), information science (IS), library science (LS), and scientometrics (MoyaAnegon et al 2006;Milojevic et al 2011;Ni and Ding 2010;Ni and Sugimoto 2011).The distinctness of the MIS cluster has led many to remove these journals from their bibliometrics analyses, arguing that they should not be included in the same JCR class (Milojevic et al 2011;Waltman et al 2011). who found that knowledge management journals are often integrated within the lists of related fields such as MIS, LS and strategic management, opined that journal ranking lists should be discipline-specific and cover only one particular area, otherwise, ranking validity may be dramatically compromised.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis also reinforces the perception that J CR 's category of IS&LS is not a cohesive grouping. Within this larger group, subfields with differing publishing and citation patterns are evident, as Ni and Ding () noted. Moreover, when clustering is based on the similarity of journal descriptions, rather than editorial board membership, different groupings appear.…”
Section: Discussionmentioning
confidence: 68%
“…However, portal: Libraries and the Academy is in the international library practice cluster. Ni and Ding's (2010) analysis of interlocking editorial board membership provides a useful comparison with Figure 5. For example, almost all the journals that do not share editorial board members appear in the international library practice cluster.…”
Section: Journal Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation